Intervention outcome differences for adult children of domestic violence - Diamond, Donna Jo (2008)
The purpose of this study was to investigate intervention outcomes for domestic violence in families and adult children. This study targeted intervention outcomes of families and adult children from domestic violence homes for the purpose of comparing those self referred versus those who were mandated for intervention